Âzyk. Poètičeskij tekst. Diskurs - Štajn, Klara E. (Stylistyka, 2002)
The article deals with the problem of self-development of the language as а system of systems. lt shows that harmonization is typical both for language system itself and artistic text, based оп the language. Harmonic organization of poetic text, coordinating artistic means af1at, upright in it's deep, leading all elements to the integrity is being examined. Studies of poetry are held, taking into consideration epistemological reality in which harmonic organization of the text and style of ап artist was fomed.